Quantification of Fetal Gyrogenesis in the Third Trimester. A Novel Algorithm for Evaluating Fetal Sulci Development. Issue 2 (3rd December 2020) - Ginsberg, Yuval; Ganor‐Ariav, Oryan; Hussein, Hadeel; Adam, Dan; Khatib, Nizar; Weiner, Zeev; Beloosesky, Ron; Goldstein, Israel
ABSTRACT: BACKGROUND AND PURPOSE: The fetal brain changes significantly throughout gestation. From a smooth (lissencephalic) cortex, it transforms into its convolved (gyrencephalic) state. Despite its importance, the diagnosis of delay in brain gyrogenesis is a challenge for many sonographers. This study presents a novel semiautomatic image processing algorithm for simple quantification of sagittal sulci maturation in the third trimester. METHODS: Mid‐sagittal fetal brain ultrasound images were obtained during routine third trimester scans. Fetal brain sulci length measurements were performed using a novel semiautomatic image processing algorithm followed by manual measurements. Correlations between the total length of the sulci, gestational age, and fetal biometry were examined. RESULTS: The study included 64 patients. A significant positive linear correlation was found between total sulci length and gestational age ( r = .658 for automated measurement, r = .7 for manual measurement, P < .0001). A similar relationship was found comparing total sulci length and fetal head circumference ( r = .694 for automated measurement, r = .74 for manual measurement; P < .0001). A significant correlation was observed between automated and manual measurements ( r = .947). CONCLUSIONS: We found that fetal gyrogenesis is linear throughout the third trimester of pregnancy. The use of a computer algorithm to measure fetal sulci can be used as a simple prenatal screening test for delayed gyral maturation of the fetal brain.